Analysis of the relationship between self-neglect and spiritual well-being in older adults - Ozturk, Zeynep; Turan, Gulcan Bahcecioglu; Donmez, Orhun (Routledge Journals, Taylor & Francis Ltd, 2025)
This study was conducted to examine the relationship between self-neglect and spiritual well-being in older adults. This descriptive, cross-sectional and correlational study was conducted with 232 older adults. Data were collected using the Elder Self-Neglect Scale (ESNS) and Spiritual Well-Being Scale (FACIT Sp-12). It was found that 54% of the participants were female, 86% were married, 35% were primary school graduates, 66% lived in the district, 27% had hypertension, 54% had income equal to expenses, and 76% were retired. Mean ESNS total score of older adults was 102.83 +/- 24.82 and mean FACIT Sp-12 total score was 33.73 +/- 9.70. FACIT Sp-12 total score was found to be a significant negative predictor of the dependent variable ESNS total score (p < .05). In this study, it was determined that the spiritual well-being levels of older adults were above average and their self-neglect levels were low. It was determined that as the spiritual well-being levels of older adults increased, their self-neglect levels decreased.
Keywords: Older adults; self-neglect; spiritual well-being